Partisipasi Lembaga Pemantau Dalam Pemilu Tahun 2019 Di Provinsi Sulawesi Utara - Paparang, Boyke Richard; Liando, Ferry Daud; Lengkong, Johny Peter (Sam Ratulangi University, 2023)
This research aims to find out how the participation of election monitoring institutions by looking at issues in monitoring. The research was conducted from March to October 2022. This research is located in North Sulawesi Province, to see the extent of the problems that exist in the monitoring process of general election institutions in 2019. The research took a qualitative descriptive method in order to provide a detailed description of the phenomenon, especially the participation of election monitors in the 2019 elections in North Sulawesi Province. This research focuses on how the participation of election monitors in the 2019 elections in North Sulawesi Province by looking at issues in monitoring. Data collection was carried out through observation, interviews, and documentation. The research used qualitative research data analysis techniques that are commonly used. The results showed that based on the aspects of Money Politics, Campaign, Quiet Period, Voting Day, Recapitulation Process, Election Accessibility Arrangements, and Voters List that they were able to carry out their duties as they should and still needed to maintain coordination in order to create a good form of communication.